2012
DOI: 10.3109/13880209.2012.711839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of total flavonoids fromDracocephalum moldavicaon the proliferation, migration, and adhesion molecule expression of rat vascular smooth muscle cells induced by TNF-α

Abstract: These data suggest that total flavonoids from D. moldavica exhibit anti-inflammatory activities, which is probably one of the underlying mechanisms of D. moldavica for clinical treatment of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, when C5a was added to untreated or C4a-pretreated macrophages and then the supernatant from macrophages was added to VSMCs, it was revealed that C5a-treated macrophages-conditioned medium, which contained cytokines TNF-α, IL-6 and chemokine MCP-1, significantly increased the migration and proliferation of VSMCs, and TNF-α further increased VCAM-1 expression in VSMCs. These results were consistent with previous studies (12,35). The increased migration, proliferation and upregulation of VCAM-1 expression were significantly suppressed when VSMCs were exposed to the conditioned medium from C4a-pretreated macrophages (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…However, when C5a was added to untreated or C4a-pretreated macrophages and then the supernatant from macrophages was added to VSMCs, it was revealed that C5a-treated macrophages-conditioned medium, which contained cytokines TNF-α, IL-6 and chemokine MCP-1, significantly increased the migration and proliferation of VSMCs, and TNF-α further increased VCAM-1 expression in VSMCs. These results were consistent with previous studies (12,35). The increased migration, proliferation and upregulation of VCAM-1 expression were significantly suppressed when VSMCs were exposed to the conditioned medium from C4a-pretreated macrophages (Fig.…”
Section: Discussionsupporting
confidence: 94%
“…Disrupting transcription activity of p50-p65 heterodimer, procyanidins decline macrophage-produced IL-6 and COX-2 via blocking LPS-initiated TLR4/NF- κ B pathway [ 99 ]. Ingredients in dracocephalum moldavica normalize the levels of VCAM-1 and ICAM-1 in VSMCs by suppressing TNF- α -triggered NF- κ B signaling [ 100 ]. Moreover, icariin reverses LPS-induced NF- κ B activation and cytokines production in macrophages via boosting PI3K/Akt pathway, whereas saponin glycyrrhizic acid and triterpenoid Ssa restrain inflammation by encumbering PI3K/Akt cascade [ 12 , 101 , 102 ].…”
Section: Mechanisms Of Action Of Chmsmentioning
confidence: 99%
“…The over-proliferation of VSMCs is one of the key factors in atherosclerosis and the restenosis following percutaneous transcoronary angioplasty (9,10). It has been reported that the flavones and flavonoids extracted from other plants inhibit the proliferation of VSMCs and leiomyomal cells (11,12). Therefore, the present study examined the effects of FDM on the proliferation of VSMCs.…”
Section: Introductionmentioning
confidence: 95%